Unlocking Development: A CAGE Policy Report (2014)
The world’s poor are ‘trapped’ in poverty. How can we unlock development so that poor countries can sustain economic growth over long periods of time? Our report considers this problem on three levels, the national economy, the private sector, and citizenship. At the core of each chapter is new research by CAGE members and associates. Chapter 1 addresses the factors underlying sustainable growth of the national economy. Chapter 2 looks for the sources of business capacity and sustainable growth of the private sector. Chapter 3 links citizenship to economic development, showing how political voice can enable women to participate more freely in society and the economy.In all three chapters we show how economic development relies on the rule of law, including a framework of laws and their enforcement that is applied to all and accessible by all. We show how, without such a framework, the sustainable growth of national economies and their businesses is threatened when laws fail to resolve conflicts. This failure is often accompanied by corruption or violence. So, we discuss what can be done to promote the rule of law; to make economic growth more stable and sustainable; to enhance the capacity of business organisations that are most likely to attract, grow and create jobs; and to enable women to play a full part in economic development as citizens, providers, and entrepreneurs.Foreword by Frances Cairncross; Introduced by Nicholas Crafts.